(untitled) (Development Service Industry Management, 2024)
The article emphasizes that the system of safety-oriented management of logistics entities is effective in establishing the modernization processes of financial-economic, organizational-management, regulatory-methodical, intellectual-personnel, information-analytical, technical-technological, institutional-legal support. As a leading characteristic of safety-oriented management of logistics entities, it is proposed to consider improving the quality of development and implementation of management decisions, which depends on a clear definition of individual subsystems in accordance with the regulatory impact on the economic, investment, technical and technological, marketing and other spheres of entrepreneurship. The achievement of efficiency, stability, stability and other factors that determine the adequacy of resource provision, the need for external borrowing and opportunities to strengthen the competitive position of the enterprise are highlighted as priority landmarks of security-oriented management of logistics activities. It was emphasized that the processes of modernization and renewal of the safety-oriented management system should take place on a permanent basis and have the necessary resource provision, which is aimed at improving the financial, economic, social and other results of entrepreneurial activity. The obtained results of the research made it possible to propose such areas of improvement of the system of safety-oriented management of logistics entities in the conditions of digitalization, such as improving resource provision for the implementation of management decisions, modernizing the structural and functional vision of management, observing basic and implementing new management principles and standards, introducing innovations and leading digital technologies into the management system.